Humeral fracture repair using a robust fixation in an adult Giant Anteater (Myrmecophaga tridactyla): case report - Minto, B.w. [UNESP]; Magalhães, T.v. [UNESP]; Lucena, D.v.f. [UNESP]; Soriano, I.m. [UNESP]; Barranco, G.h.f. [UNESP]; Dias, L.g.g.g. [UNESP]; Werther, K. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
The treatment of fractures from the thoracic limb in giant anteaters is extremely challenging. Unfamiliar and peculiar anatomical characteristics, robust musculature and the imminent need for an early return to limb function highlight such challenges. The objective of this report was to describe the successful use of anatomical osteosynthesis with a robust locking compression plate in a humeral fracture of an adult giant anteater. The patient was rescued on the highway after being run over and presented for treatment at the Veterinary Teaching Hospital. Surgical stabilization was performed using a craniomedial approach to the humerus, using a customized broad 3.5mm locking compression plate. The patient presented early limb support at 24 hours postoperatively. Radiographic monitoring was performed at 30, 60 and 90 days postoperatively, and bone healing was observed without any complications. It is concluded that the treatment of humerus fractures in giant anteaters requires robust fixation. The use of a reinforced locking compression plate system proved to be effective and adequate to the mechanical load that an adult individual of this species needs for early use of the thoracic limb and, at the same time, efficient in controlling interfragmentary movement, which allowed fracture consolidation.

O tratamento das fraturas do membro torácico dos tamanduás-bandeira (Myrmecophaga tridactyla) é extremamente desafiador. Características anatômicas pouco familiares e peculiares, musculatura muito desenvolvida e necessidade iminente de retorno precoce à função do membro destacam tais desafios. Objetivou-se, neste relato, descrever a utilização com sucesso da osteossíntese anatômica com placa bloqueada robusta em fratura umeral de um tamanduá-bandeira. O paciente foi resgatado em rodovia após atropelamento e atendido no Hospital Veterinário Universitário. Após sedação e avaliação física completa, foi realizado exame radiográfico, o qual revelou fratura completa oblíqua curta em diáfise média de úmero esquerdo. A estabilização cirúrgica foi realizada por abordagem craniomedial ao úmero, utilizando-se placa bloqueada (LCP) do sistema 3,5mm customizada. O paciente apresentou apoio precoce do membro com 24 horas de pós-operatório. Realizou-se acompanhamento radiográfico aos 30, 60 e 90 dias, sendo observada união clínica sem quaisquer complicações. Conclui-se que o tratamento das fraturas do úmero em tamanduás-bandeira exige robustez na fixação. A utilização de sistema reforçado de placa bloqueada mostrou-se efetiva e adequada à carga mecânica de que um indivíduo adulto dessa espécie necessita para uso precoce do membro torácico e, ao mesmo tempo, eficiente no controle da movimentação interfragmentária, o qual permitiu consolidação da fratura.
[Reparo de fratura umeral usando uma fixação robusta em um tamanduá-bandeira adulto (Myrmecophaga tridactyla): relato de caso]
Keywords: bone consolidation; orthopedics; osteosynthesis; wild animal; consolidação óssea; ortopedia; osteossíntese; silvestres